Coffee Shop Marketing Communication Strategy to Increase Sales (Case Study at Kedai Kopi Inspirasi Bogor) - Adi Nur Fatah; Hedi Pudjo Santosa (PT Mattawang Mediatama Solution, 2023)
Kedai Kopi Inspirasi is a well-known coffee shop in Bogor Regency, as shown by the high number of visitors and exposure in various local media as one of the recommendations for coffee shops in Bogor Regency. The purpose of this research is to discover how Kedai Kopi Inspirasi may use marketing communication strategies to boost customer sales and visits in the midst of fierce competition in the present coffee shop business. The data for this research was collected through interviews with the owners and management of Kedai Kopi Inspirasi observation, and literature reviews. The theory used for this research is Integrated Marketing Communication with a Promotion Mix. Based on data analysis, it was found that Kedai Kopi Inspirasi had implemented a marketing communication strategy as part of their promotional strategies, utilizing advertising, personal selling, sales promotion, and public relations strategies to raise brand awareness, which resulted in higher customer visits and purchases. In order to attract customers in the Jabodetabek area, Kedai Kopi Inspirasi performs social media marketing. In addition, personal selling is conducted through engaging with customers as a type of service in order to encourage up-selling in every interaction. Sales promotions are performed by offering special deals on specific holidays. Simultaneously, Kedai Kopi Inspirasi works to approach particular groups and organizations for public relations purposes and may later take part in an event to attract potential customers